2012
DOI: 10.4236/ojepi.2012.23011
|View full text |Cite
|
Sign up to set email alerts
|

“Quito municipal schools” cohort study: Baseline results

Abstract: The lack of population-level data on growth and development of children and adolescents in Ecuador, and the existence of previous data suggesting an alarming increase in the numbers of children presenting overweight or obesity justifies the present cohort study which includes all pupils of municipal schools of Quito aged 9 to 17 years. Follow-up will continue for a minimum of 7 years. This will allow determining the evolution of prevalence of these phenomena and their trends as well as other indices, both phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The Quito research team developed a self-administered questionnaire. Compliance with ethical considerations and criteria of inclusion and exclusion have been explained elsewhere [4].…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Quito research team developed a self-administered questionnaire. Compliance with ethical considerations and criteria of inclusion and exclusion have been explained elsewhere [4].…”
Section: Populationmentioning
confidence: 99%
“…As with any chronic health problem it is very difficult to take preventive measures without knowing how it is perceived by those most affected, in this case children and adolescents. The study entitled "Quito municipal schools cohort study: Baseline results" investigating 6964 pupils between their sixth and tenth year of basic education during the 2010-2011 academic year, reported that 18.7% (CI 95% 17.8 -19.6) were overweight, and 7.9% (CI 95% 7.6 -8.2) were obese (excess weight: 26.6%) (Natalia Romero-Sandoval et al, 2012) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Weight status: This variable had three categories following WHO criteria for each age and sex based on the 85th and 97th BMI percentiles (BMI > P97 equal Obesity, P85<BMI<P97 Overweight, the rest "normal"). In order to analyse the overall phenomenon of excess weight, we created a dichotomised variable representing "excess weight" by combining the original categories of 'overweight' and 'obese'; that is categories Obesity and Overweight equal "yes" and the rest equal "no" [14].…”
Section: Variablesmentioning
confidence: 99%
“…The prevalence of overweight found in the 6964 participants aged from 9 to 17 years was 18.7%, (CI 95% = 17.8 -19.6) and of obesity was 7.9%(CI 95% = 7.3 -8.5); in most ages overweight and obesity was more common in boys than in girls. 62.3% of students reported living in a family nuclear (consisting of parents and children) and 60.5% said that their families were in the "teenager" stage (families whose first born child was now a teenager) [14].…”
Section: Introductionmentioning
confidence: 99%